2019
DOI: 10.1021/acs.jpcb.9b01057
|View full text |Cite
|
Sign up to set email alerts
|

State of Oxygen Molecules in Aqueous Supersaturated Solutions

Abstract: The state of oxygen in aqueous supersaturated solutions prepared by different methods was studied using highresolution ultrasonic spectroscopy in combination with other techniques. This allowed for nondestructive evaluation of the properties of oxygen solute particles, composed of oxygen molecules and surrounding (coordinating) molecules of water, at equilibrium, supersaturated conditions, and different temperatures and concentrations of O 2 . The results were compared with the behaviors of other types of solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 138 publications
(250 reference statements)
0
6
0
Order By: Relevance
“…Oxygen transport across the bilayer structure depends on both diffusion and solubility in the bilayer, which is closely related to the content of cholesterol and unsaturated fatty acids on the cell membrane (Möller et al, 2016;Li and Buckin, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Oxygen transport across the bilayer structure depends on both diffusion and solubility in the bilayer, which is closely related to the content of cholesterol and unsaturated fatty acids on the cell membrane (Möller et al, 2016;Li and Buckin, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in the case of DO meter 3, it was also confirmed that the value tended to decrease when the bubbles adhered to the sensor surface. Fig 4A shows that DO meter 3 could measure the oxygen content in the FB dispersions; however, it was necessary to pay attention to the position and orientation of the sensor for avoiding the bubble adhesion to the sensor surface [ 27 ]. Therefore, it is difficult to directly measure the oxygen content in FB dispersions with conventional DO meters, particularly in areas where MBs and macro bubbles are continuously generated.…”
Section: Resultsmentioning
confidence: 99%
“…In recent studies, dissolved oxygen (DO) meters [ 2 , 9 ], a blood gas analyzer [ 24 ], and a titration method (Winkler’s method) [ 17 , 26 ] have been used to measure the oxygen content in FB dispersions under the temperature region from 20°C to 30°C. Although the two former methods can provide data quickly and easily, the accuracy is concerned when FBs attach to the surface of their electrodes [ 27 ], and it should be noted that the oxygen content in the gas phase of the FBs is not included in the outcome. Moreover, conventional DO meters cannot measure dissolved oxygen concentrations of above 50 mg/L.…”
Section: Introductionmentioning
confidence: 99%
“…While there are some experiments monitoring dissolved oxygen with probe-type oxygen electrodes in large containers where FBs generate, it is difficult to conduct a small-scale experiment that allows precise management of experimental conditions. Furthermore, some papers suggested that the adhesion of bubbles to the electrode surface is an important issue when using probe-type oxygen electrodes that are used for a quick and easy method to measure dissolved oxygen in water. , Therefore, we developed a novel method for measuring the oxygen content in FB dispersions that satisfied the criteria of accuracy, ease (four steps), small sample volume (50–500 μL), and quickness (<8 min) without the adhesion issue . Moreover, FB dispersion at 20 °C has oxygen above 50 mg/L, and our method can measure the range that cannot be measured with probe-type dissolved oxygen meters.…”
Section: Introductionmentioning
confidence: 99%